The relationship of Personality Traits and Academic and Social Self Efficacies of Learning Disabilities (LD) Learners - Hamid, Norazlem Abd; Echee, Moop; Benlahcene, Abderrahim; Lubana, Anita (South Asian Journal of Social Sciences and Humanities, 2020)
This paper examined the relationship between Big Five personality traits (OCEAN) and academic and  social self-efficacies of learning disabilities (LD) learners. A total of 89 LD learners aged 10 to 19 years  old completed questionnaires measuring Big-Five personality traits (International Personality Item Pool,  IPIP), academic self-efficacy (Academic Efficacy scale from the Manual for the Patterns of Adaptive  Learning Scales, MPAL), and social self-efficacy (Social Competence Rating Scale for Children, SCRSC).  Pearson correlation shows that personality traits that have a significant relationship with academic and  social self-efficacies were openness, conscientiousness, extraversion, and agreeableness while neuroticism  does not have a significant relationship with both academic and social self-efficacies. Implications for  future intervention are also being discussed.
Keywords: Big Five personality; learning disabilities; academic self-efficacy; social self-efficacy